1999
DOI: 10.1159/000026604
|View full text |Cite
|
Sign up to set email alerts
|

Smoking History and Aging-Associated Cognitive Decline:An Event-Related Brain Potential Study

Abstract: Although cigarette smoking has been associated with reduced risk for dementia of the Alzheimer type, relatively little is known about the central impact of a lengthy smoking history, particularly with respect to the cognitive effects, on the normal aging brain. Given that elderly adults have been reported to exhibit poor short-term memory in conditions requiring divided attention, this study utilized behavioral performance and event-related potential (ERP) measures to compare groups (n = 10/group) of young (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…Such data were also observed in research 20 in which the latency of wave III showed higher values in the group of smokers when…”
Section: Wavessupporting
confidence: 74%
“…Such data were also observed in research 20 in which the latency of wave III showed higher values in the group of smokers when…”
Section: Wavessupporting
confidence: 74%
“…Similarly, recent laboratory studies of brain function via quantitative electroencephalography (EEG) or event-related potentials (ERP) did not evidence any marked differences between elderly lifelong nonsmokers and smokers. 21,22 Contrary to these negative findings, some longitudinal studies suggested smoking as an isolated predictor of cognition. A French cohort study 23 showed some benefits of smoking on attentional and visuospatial functioning, but dose effect was unavailable.…”
Section: Discussionmentioning
confidence: 94%
“…Given that the paradigm used in the present study is identical to that used by Schrö ger and Wolff (1998a), we can speculate that these behavioral performance discrepancies may be specific to smokers or may reflect altered cognitive processes resulting from chronic tobacco use or acute (tobacco) abstinence-related withdrawal. Evidence for altered cognition with smoking withdrawal is substantial (Heishman et al, 1994), and although systematic research on the lasting effects of tobacco use on cognition is lacking, a few P300 studies suggest that prolonged smoking history can alter higher order processes (Anokhin et al, 2000;Knott, Harr & Mahoney, 1999). Mechanisms underlying the tone type 6 duration interaction in smokers are open to speculation, but it is possible that for smokers, who are characterized as being electroencephalographically hypoaroused during smoking abstinence (Knott & Venables, 1977), the novelty of the short deviant tones (vs. short standard tones) may have induced a phasic alertness or arousal increment that indirectly enhanced selective processes (Water & Sutton, 2000).…”
Section: Discussionmentioning
confidence: 99%